A Descriptive Study Using the Comprehensive Race Socialization Inventory: Findings From the National Survey of American Life-Adolescent Supplement. (March 2020) - Brown, Tony N.; Culver, Julian; Wilkins, Kiana; Gorman, Quintin; Bento, Asia; Alvis, Aly M.; Lesane-Brown, Chase L.; Caldwell, Cleopatra Howard
This study examines race socialization, defined as the process whereby individuals learn about the meaning and significance of race and racism. With data from the 2001–2004 National Survey of American Life-Adolescent Supplement (NSAL-A), we analyze responses to the Comprehensive Race Socialization Inventory (CRSI) among 1, 170 African American and Caribbean Black adolescents between the ages of 13 and 17 years. The CRSI captures sources, frequency, content of messages, and prevalence of the most useful message, among other components (e.g., onset and recency, anticipatory socialization, and socializing behaviors). We find 90% of respondents report someone talked with them about what being Black means. In addition, most respondents report receiving messages from all four sources specified in the CRSI (i.e., parents, relatives, friends, and other adults). We find little evidence to suggest sources differ by sex, age, ethnicity, or U.S. region. The question assessing the most useful message is open-ended. Over 60% of respondents recall content supporting "Race equality, " maintaining a "Positive self-attitude, " or emphasizing "Black pride" as the most useful message. We conclude race socialization is commonplace among Black adolescents because racism necessitates it.